Identity and Practices of Buddhist Laity in Tipiṭaka: An Analysis of the Concepts of Upāsaka and Upāsikā - Medhacitto, Tri Saputra; Sukodoyo, Sukodoyo; Kustiani, Kustiani (AL-ADYAN, 2026)
This study examines the concepts of upāsaka and upāsikā in Tipiṭaka in order to construct a comprehensive understanding of the identity and practice of Buddhist lay adherents. The research adopts a library-based methodology, drawing on primary sources from Tipiṭaka and its commentaries, as well as secondary sources comprising peer-reviewed journal articles, scholarly books, and academic publications relevant to the topic. Content analysis is employed to systematically identify, classify, and interpret the meanings and practices associated with upāsaka and upāsikā within Buddhist canonical texts, particularly the Dīgha Nikāya, Majjhima Nikāya, Saṃyutta Nikāya, Aṅguttara Nikāya, Dhammapada, and Sutta Nipāta. The analytical procedure follows the stages of data reduction, data display, and conclusion drawing. The findings elucidate the definition of upāsaka and upāsikā, the formation process of lay Buddhist identity, the normative practices prescribed for lay adherents, and the conditions required for establishing an orthodox lay Buddhist identity.